2009
DOI: 10.1242/dev.034959
|View full text |Cite
|
Sign up to set email alerts
|

The Integrator subunits function in hematopoiesis by modulating Smad/BMP signaling

Abstract: *Hematopoiesis, the dynamic process of blood cell development, is regulated by the activity of the bone morphogenetic protein (BMP) signaling pathway and by many transcription factors. However, the molecules and mechanisms that regulate BMP/Smad signaling in hematopoiesis are largely unknown. Here, we show that the Integrator complex, an evolutionarily conserved group of proteins, functions in zebrafish hematopoiesis by modulating Smad/BMP signaling. The Integrator complex proteins are known to directly intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…wnk1a and wnk1b mRNAs are maternally deposited, and zygotic expression of both begins as early as 10 hpf (hours post fertilization) and remains high at all stages examined. The expression of flk1/vegfr2 begins as early as the 5 to 9 somite stage (12 to 15 hpf) in the intermediate cell mass of the mesoderm [40] and the 14 to 19 somite stage (16 to 19 hpf) in the head and vessel endothelial cells [41]. Additional studies have reported that flk1/vegfr2 is expressed in the intersegmental vessels at 24 hpf [42] when the single circulatory loop in zebrafish is established [43], [44].…”
Section: Resultsmentioning
confidence: 99%
“…wnk1a and wnk1b mRNAs are maternally deposited, and zygotic expression of both begins as early as 10 hpf (hours post fertilization) and remains high at all stages examined. The expression of flk1/vegfr2 begins as early as the 5 to 9 somite stage (12 to 15 hpf) in the intermediate cell mass of the mesoderm [40] and the 14 to 19 somite stage (16 to 19 hpf) in the head and vessel endothelial cells [41]. Additional studies have reported that flk1/vegfr2 is expressed in the intersegmental vessels at 24 hpf [42] when the single circulatory loop in zebrafish is established [43], [44].…”
Section: Resultsmentioning
confidence: 99%
“…Based upon these criteria, we asked whether the Integrator, which is a metazoan-specific RNAPII-associated multi-protein complex, might fulfill the role of the RNAPII pause release factor following EGF transcriptional activation. We had previously characterized Integrator as a multi-subunit complex that was required for the maturation of the small nuclear RNA genes (Baillat et al, 2005) but the number of studies describing the wide array of developmental defects and diseased states upon its dysfunction suggest its scope may extend beyond the biosynthesis of snRNA (Han et al, 2006; Kapp et al, 2013; Tao et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…RNAi-mediated depletion of IntS6 in Caenorhabditis elegans results in embryonic lethality and mitochondrial defects (15), whereas depletion of IntS5 in zebrafish using antisense morpholino oligonucleotides also results in lethality and defects in hematopoiesis (50). Finally, targeted disruption of the gene encoding mouse IntS1 results in early embryonic lethality and the accumulation of snRNA precursors (16).…”
Section: Discussionmentioning
confidence: 99%